2016
DOI: 10.1007/s10554-016-0853-9
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of renal arteries after radio-frequency catheter-based denervation using optical coherence tomography and angiography

Abstract: Optical coherence tomography (OCT) imaging at the time of renal denervation (RDN) showed that procedure might cause spasm, intimal injury or thrombus formation. In the present study, we assessed the healing of renal arteries after RDN using OCT and renal angiography in long-term follow-up. OCT and renal angiography were performed in 12 patients (22 arteries) 18.41 ± 5.83 months after RNS. There were no adverse events or complications during the long-term follow-up. In ten patients (83 %), significant reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
0
4
0
2
Order By: Relevance
“…This has been confirmed in a study conducted on beagles [8,9]. Moreover, direct stimulation using RF energy as well as the use of catheter and wire on the arterial intima may cause intimal injury and/or thrombosis [10,11], which may trigger the progression of atherosclerosis. To minimize these side effects, we found that laparoscopicbased perivascular RDN was effective in controlling the BP and allowed for a decrease in the amount of antihypertensive drugs.…”
Section: Discussionmentioning
confidence: 71%
“…This has been confirmed in a study conducted on beagles [8,9]. Moreover, direct stimulation using RF energy as well as the use of catheter and wire on the arterial intima may cause intimal injury and/or thrombosis [10,11], which may trigger the progression of atherosclerosis. To minimize these side effects, we found that laparoscopicbased perivascular RDN was effective in controlling the BP and allowed for a decrease in the amount of antihypertensive drugs.…”
Section: Discussionmentioning
confidence: 71%
“…Despite the failure of the SYMPLICITY HTN‐3 trial to meet its primary efficacy end point, recent positive results from the SPYRAL HTN‐ON MED 22 and RADIANCE‐HTN SOLO 23 trials sparked our interest in studying the denervation methods. However, we believed that direct stimulation using RF energy and the use of catheter and wire on the arterial intima could result in intimal injury and/or thrombosis, 13,24 which may trigger the progression of atherosclerosis. Moreover, an inappropriate ablation device may lead to inadequate ablation, which in turn results in uncertainty in the effects of RDN 14 …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the problems associated with this procedure should not be ignored. Currently, although the number of patients who undergo percutaneous endovascular RDN is limited and the follow-up period is short, some side effects have been reported [15], i.e., lumen stenosis, atrial wall hematoma, intimal tears, intraluminal thrombosis, intima-media thickening [16][17][18][19], etc. Most of these factors may be caused by the direct delivery of RF energy or stimulation of the endothelium by the wire and catheter.…”
Section: Discussionmentioning
confidence: 99%